Pengaruh Pelatihan dan Lingkungan Kerja Terhadap Motivasi Kerja Karyawan - Wibowo, Sri; Arqy Ahmadi, Mirzam (Teewan Journal Solutions, 2025)
Organizations in the era of globalization must improve their performance and productivity aspects to survive and remain competitive. Work motivation is an important factor in influencing organizational performance. The work environment and training are said to be able to significantly influence employee work motivation. This study examines the influence of training and work environment on employee work motivation in the context of organizations in Indonesia. Utilizing a qualitative method with a literature-based approach, this research analyzes current literature on human resource management, organizational psychology, and organizational behavior. The findings indicate that effective and relevant training significantly contributes to increasing employee work motivation through enhanced skills, self-confidence, and job satisfaction. A conducive work environment, both physical and non-physical, is also proven to have a positive impact on work motivation. Another crucial finding is the complex interaction between training and work environment in influencing employee motivation, where a supportive work environment can reinforce the positive effects of training. In the Indonesian context, cultural factors such as collectivism and social hierarchy play important roles in how employees respond to training and perceive their work environment. This research also emphasizes the importance of adapting to post-COVID-19 pandemic changes, including virtual training and the creation of supportive digital work environments. In conclusion, organizations in Indonesia need to adopt a holistic and contextual approach in designing training programs and managing work environments to effectively enhance employee work motivation. Practical implications and recommendations for future research are also discussed.